2010
DOI: 10.3814/2010/736039
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Convection Boundary Layer Flow from a Solid Sphere with Newtonian Heating in a Micropolar Fluid

Abstract: The steady mixed convection boundary layer flow from a solid sphere in a micropolar fluid, generated by Newtonian heating in which the heat transfer from the surface is proportional to the local surface temperature, is considered. The governing boundary layer equations are first transformed into a system of nondimensional equations via the non-dimensional variables, and then into nonsimilar equations before they are solved numerically using an implicit finite-difference scheme known as the Keller-box method. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The results are obtained in terms of velocity profiles, temperature distributions, skin friction coefficient, and the rate of heat transfer and presented graphically and tabular form for selected values of the thermal radiation parameter, Darcy number, Newtonian heating parameter, and the pressure stress work. In order to verify the accuracy of the present method, the present results are compared with those reported by Salleh et al [18]. It is found that the agreement between the previously published results with the present ones is very good, as shown in the tab.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…The results are obtained in terms of velocity profiles, temperature distributions, skin friction coefficient, and the rate of heat transfer and presented graphically and tabular form for selected values of the thermal radiation parameter, Darcy number, Newtonian heating parameter, and the pressure stress work. In order to verify the accuracy of the present method, the present results are compared with those reported by Salleh et al [18]. It is found that the agreement between the previously published results with the present ones is very good, as shown in the tab.…”
Section: Resultssupporting
confidence: 79%
“…Table 1. Comparisons of the present numerical results of C f for the Pr = 0.7, 1, and 7.0 without effect of the thermal radiation-conduction, stress work, and porous medium with those obtained by Salleh et al [18] x Pr = 0. The effect of radiation parameter on skin friction and rate of heat transfer, Nu, are considered in tab.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…Pop et al [11] presented results for the problem of free convection boundary layer flow along a vertical surface in a porous medium with newtonian heating. Recently, Salleh et al [12][13][14][15] studied the free and mixed convection boundary layer flows past a sphere with Newtonian heating in a viscous and micropolar fluid using the Keller-box method.…”
Section: Introductionmentioning
confidence: 99%